Running scared - Foster, David; Turman, Lawrence; Hyams, Peter (Santa Monica, California MGM Home Entertainment, 1986)
Ray and Danny are the wild men of the Windy City's police force. The pair's worthodox methods get results in a tough town - until they come up against Julio Gonzales (Jimmy Smits, "NYPD Blue"), a smooth-talking drug dealer who is bucking to become Chicago's first Spanish Godfather. Trying to nail Gonzales, they blow a delicate undercover operation and are sent on a forced vacation to Key West - where they discover the good life of warm weather and warmer women. The new locale makes them decide to retire...but not before putting Gonzales behind bards first.
Music by, Rod Temperton ; Screenplay and story by, Gary Devore and Jimmy Huston ; Executive producer, Peter Hyams.
Gregory Hines, Billy Crystal, Steven Bauer.
Dolby digital.
In English.
Keywords: Comedy films